Implementasi Pembelajaran Daring Terhadap Prestasi Siswa Kelas 3 Pada Mata Pelajaran Tematik di SDN Kedunggalar IV - Fitri Nurul Hidayah; Prima Rias Wana; Djoko Hari Supriyanto (Universitas PGRI Adi Buana Surabaya, 2021)
This study aims to see and describe the implementation of brave learning during the pandemic on the achievements of third grade students at SDN Kedunggalar 4 Kedunggalar District Ngawi. This study uses a qualitative descriptive. Data collection techniques in this study are observation, and interviews. Interviews were conducted with the principal, class teacher, and third grade students at SDN Kedunggalar 4. The results of this study were that during the learning process the courage to use video went well, before learning began the teacher made a lesson plan, carried it out, made an assessment that included affective cognitive and psychomotor aspects. . Increasing student achievement is very good, because students are not only easy to carry out learning, the material provided by the teacher can be repeated, so that students better understand the material that has been given by the teacher.